AKIBAT HUKUM WANPRESTASI KREDITUR TERKAIT PENYERAHAN SERTIPIKAT YANG MENJADI JAMINAN KREDIT PEMILIKAN RUMAH - Indah, Syiva Puspa; Sudirman, Maman; Fitrian, Achmad (Case Law : Journal of Law, 2025)
The research aims to analyze the legal consequences of creditors for failure to submit mortgage guarantee certificates that have been paid off which are analyzed using collateral law theory. The research method uses normative juridical with a statutory approach, conceptual approach, analytical approach, and case approach. The technique for collecting legal materials is carried out by identifying and inventorying positive legal rules, book literature, journals and other sources of legal materials. The analysis technique for legal materials is carried out using grammatical and systematic legal interpretation, as well as the analogous legal construction method. The research results concluded that the legal consequences of a creditor's default in submitting a KPR guarantee certificate that has been paid off violates Article 1238 of the Civil Code and can harm the debtor. The debtor has the right to demand that the bank immediately submit the certificate and, if this is not fulfilled, can sue through legal channels, either through a lawsuit for breach of contract (Article 1243 of the Civil Code) or an unlawful act (Article 1365 of the Civil Code). If the debtor experiences losses due to delays in submitting the certificate, the bank may be required to pay compensation